Answer:
0.125
Step-by-step explanation:
Answer: The product of (-a + 3)(a + 4) is: -a^2-a+12
Step-by-step explanation:
(-a+3)(a+4) = -a*a-a*4+3*a+3*4
=-a^{2} -4a+3a+12
now just simply combine..
=-a^2-a+12
the answer is -a^2-a+12
Answer:
x = 4
Solution:
Combine like terms and simplify.
You would end up at (3,-1)
moving left and right is the x
moving up and down is the y
8y-4x=2x+12y
x+2y+8y-4x=180
10y-3x=180
x+2y+2x+12y=180
14y+3x=180
24y=360
y=15
8(15)-4x=2x+12(15)
120-4x=2x+180
120=6x+180
-60=6x
x=-10